POLYMERIZED SILICON (SiO2·nH2O) IN EQUISETUM ARVENSE: POTENTIAL NANOPARTICLE IN CROPS - Víctor García-Gaytán; Emanuel Bojórquez-Quintal; Fanny Hernández-Mendoza; Dhirendra K. Tiwari; Nestor Corona-Morales; Zahrabeigom Moradi-Shakoorian (Journal of the Chilean Chemical Society, 2019)
All technological innovation that influences research to achieve yields and counteract biotic and abiotic stress in crops should be a priority for governments and scientists around the world. Silicon nanoparticles (NpSi) in the production and protection of crops are used as a sustainable strategy. In addition to NpSi, other nanoparticles have been applicable in areas such as environmental remediation, medicine and smart sensors. There are plants that accumulate high concentrations of Si in their tissues, such as “horsetail” (Equisetum arvense). A recent analysis of the elemental composition of E. arvense in a cross section, epidermis, and total biomass indicated that the Si concentration was higher in comparison with macro and micronutrients. Elemental mapping showed that all polymerized silicon (SiO2 · nH2O) is available in the epidermis of Equisetum. Currently, our team is investigating the extraction, purification and quantification of SiNp. The lines of emerging research should be those related to the interaction of SiNp in the cell wall, concentration and intelligent application with aerial equipment in crops such as vegetables, cereals, and fruits.